Download presentation

Presentation is loading. Please wait.

Published byAshlynn Carr Modified over 4 years ago

2
1S Algebra Revision!

9
$100 $200 $300 $400 $500 $100 $200 $300 $400 $500 $100 $200 $300 $400 $500 $100 $200 $300 $400 $500 $100 $200 $300 $400 $500 $100 $200 $300 $400 $500

10
2a + 6f – 7a - f

11
-5a + 5f

12
5t 2 + 7t – 5t + 4t 2

13
9t 2 + 2t

14
6ac x 5a 4

15
30a 5 c

16
(2a 5 ) 3

17
8a 15

18
30x 4 y 2 / 5x 3 y

19
6xy

20
-3 (x + 7)

21
-3x -21

22
2ab(4a – 2b)

23
8a 2 b – 4ab 2

24
(a + 5)(a – 4)

25
a 2 + a - 20

26
(4a – 3)(5 + a)

27
4a 2 + 17a - 15

28
(6 – 2a)(3 + b)

29
18 + 6b – 6a – 2ab

30
5a + 10

31
5(a + 2)

32
3a + 6f – 3g

33
3(a + 2f – g)

34
15a 2 b – 3ab 2

35
3ab (5a – b)

36
a 2 + 16a + 64

37
(a + 8) 2

38
c 2 - 49

39
(c + 7)(c – 7)

40
c / 4 = 3

41
c = 12

42
2a – 4 = -14

43
a = -5

44
-3m = -27

45
m = 9

46
4x + 2 = x - 7

47
x = -3

48
15 – 2x = 17 – 3x

49
x = 2

50
a = 3, 2a + 1 = ?

51
7

52
x = 4, x 2 – 3x = ?

53
4

54
m = 2, p = 4 2m – 3p = ?

55
-8

56
r = -3 and t = -1 3r / (t + 5) = ?

57
-9/4

61
4b + 6 = 14

62
b = 2

63
(x + 4)(x – 3) = 0

64
x = -4 and x = 3

65
(2a + 6)(a – 2) = 0

66
a = -3 and a = 2

67
(4a + 2) / 9 = 2

68
a = 4

69
c 2 + 5c + 6 = 0

70
ie (c + 3)(c + 2) = 0, so c = -3 and -2

79
$200 $400 $600 $800 $1000 $200 $400 $600 $800 $1000 $200 $400 $600 $800 $1000 $200 $400 $600 $800 $1000 $200 $400 $600 $800 $1000 $200 $400 $600 $800 $1000

Similar presentations

© 2019 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google